A hot subdwarf-white dwarf super-Chandrasekhar candidate supernova Ia progenitor - Pelisoli, Ingrid; Neunteufel, P.; Geier, S.; Kupfer, T.; Heber, Ulrich; Irrgang, Andreas; Schneider, David; Bastian, A.; Van Roestel, J.; Schaffenroth; Barlow, B. N. (Nature Astronomy, 2021)
Supernovae Ia are bright explosive events that can be used to estimate cosmological distances, allowing us to study the expansion of the Universe. They are understood to result from a thermonuclear detonation in a white dwarf that formed from the exhausted core of a star more massive than the Sun. However, the possible progenitor channels leading to an explosion are a long-standing debate, limiting the precision and accuracy of supernovae Ia as distance indicators. Here we present HD 265435, a binary system with an orbital period of less than a hundred minutes that consists of a white dwarf and a hot subdwarf, which is a stripped core-helium-burning star. The total mass of the system is 1.65 +/- 0.25 solar masses, exceeding the Chandrasekhar limit (the maximum mass of a stable white dwarf). The system will merge owing to gravitational wave emission in 70 million years, likely triggering a supernova Ia event. We use this detection to place constraints on the contribution of hot subdwarf-white dwarf binaries to supernova Ia progenitors.
CRIS-Team WoS Importer:2021-07-23